Developing and Maintaining Collaborative Communities of Practice in Art, Design & Media: The North West Network Experience - Barbara E Thomas; Jill Fernie-Clarke (Educational Futures)
This paper describes and explores the methodologies underpinning the development of the North West Network of the Higher Education Academy’s Art, Design & Media Subject Centre(ADM-HEA). Founded in 2006 the networks members are drawn from a range of institutions across the North West(NW) including pre and post ’92 Universities and Further Education (FEC) Colleges with Higher Education (HE) provision. To date it has completed and disseminated two major collaborative research projects looking at research informed teaching and aspects of the student experience. The network provides opportunities for staff working at different levels, in different areas of the sector, to work together, to share good practice and to feed these experiences into teaching. It provides a model of co-operation which circumvents the problems posed by increasing competition between institutions, the difficulties presented by limited funding, and time constraints. Here, in order to promote debate about the hierarchies and perceived barriers to collaboration, are outlined the means by which the group has been sustained; the network’s research has been achieved; and the ethos of the group developed. The projects outlined here demonstrate that it is possible to provide opportunities for staff working at different levels, in different areas of the sector, to work together to undertake research and to share good practice.